Yêu cầu và giải pháp phát triển hệ sinh thái học tập sáng tạo trên địa bàn thành phố Hà Nội trong “kỷ nguyên vươn mình của dân tộc” - Nguyễn, Anh Tuấn; Đinh, Thị Kim Thương; Nguyễn, Kim Sơn (Tạp chí Giáo dục, 2025)
In the context of an educational paradigm shift toward the holistic development of learners’ competencies, creative thinking has increasingly emerged as a core requirement of contemporary education systems. Stemming from the pressing need to foster creative competency in the “Era of National Revitalization,” particularly within a major educational center such as Hanoi, this study systematically examines and delineates specific requirements concerning learners, learning knowledge, learning technologies, learning environments, culture, institutions, and creative strategies. Based on a comprehensive literature review and policy analysis, this paper proposes synchronous and integrated solutions to enhance the capacity of learning subjects, innovate knowledge content, develop appropriate technology, create a conducive learning context, and build a supportive culture and institutional framework for creativity. This study provides a systematic framework for developing a creative learning ecosystem in large cities, contributing to training high-quality human resources to meet the development requirements of Vietnam in general and the capital Hanoi in particular.